Immunity and Extracellular Matrix Characteristics of Breast Cancer Subtypes Based on Identification by T Helper Cells Profiling - Zhou, Yan; Tian, Qi; Gao, Huan; Zhu, Lizhe; Zhang, Ying; Zhang, Chenchen; Yang, Jiao; Wang, Bo (Frontiers in Immunology, 2022)
Background: Immune characteristics of breast cancer including gene characteristics and tumor infiltrating lymphocytes have become significant biomarkers for predicting prognosis and immunotherapy response in recent years. Methods: Breast cancer samples from TCGA and GSE31519 in GEO database were extracted and clustered based on gene sets representing TH cells signatures. CIBERSORT simulations of immune cell components in the tumor microenvironment and GSEA analysis were performed in the different clusters to verify the classification of the subtypes. The acquisition of DEGs in the different clusters was further used for GO and KEGG analyses. The clinical information from different clusters was used for survival analysis. Finally, the surgical tissues of TNBC samples were stained by immunofluorescence staining and Masson's trichrome staining, which to explore the correlation of TH cell subtypes with extracellular matrix (ECM). Results: The breast cancer samples were classified into TH-activated and TH-silenced clusters, which was verified by the immune cell components and enriched immune-related pathways. The DEGs of TH-activated and TH-silenced clusters were obtained. In addition to TH cells and other immune-related pathways, ECM related pathways were enriched by DEGs. Furthermore, the survival data of TCGA samples and GSE31519 samples showed that the 10-year overall survival of TH-activated cluster was better. Fluorescent labeling of TH cell subtypes and staining of collagen area of surgical specimens further illustrated the relationship between TH cell subtypes and ECM in breast cancer, among which high TH1 infiltration was related to low collagen content, while high TH2 and Treg infiltration ones contained more abundant collagen in TNBC. With regards of relationship of TH cell subtypes, TH2 was positively correlated with Treg, while TH1 was negatively correlated with both of them. Conclusions: The immune and ECM characteristics of breast cancer subtypes based on TH cells characteristics were revealed, and the relationship associated different TH cell subsets with ECM and prognosis were explored in this study. The crosstalk between ECM and TH cell subtypes formed a balanced TME influencing the prognosis and treatment response in breast cancer, which suggests the correlation between TH cell and ECM needs to be further emphasized in future breast cancer studies.